Evaluation of several ultrasonography scoring systems for synovitis and comparison to clinical examination: results from a prospective multicentre study of rheumatoid arthritis. Issue 5 (9th September 2009) - Dougados, Maxime; Jousse-Joulin, Sandrine; Mistretta, Frederic; d'Agostino, Maria-Antonietta; Backhaus, Marina; Bentin, Jacques; Chalès, Gérard; Chary-Valckenaere, Isabelle; Conaghan, Philip; Etchepare, Fabien; Gaudin, Philippe; Grassi, Walter; et al.
Abstract : Objectives: To evaluate different global ultrasonographic (US) synovitis scoring systems as potential outcome measures of rheumatoid arthritis (RA) according to the Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) filter. Methods: To study selected global scoring systems, for the clinical, B mode and power Doppler techniques, the following joints were evaluated: 28 joints (28-joint Disease Activity Score (DAS28)), 20 joints (metacarpophalangeals (MCPs) + metatarsophalangeals (MTPs)) and 38 joints (28 joints + MTPs) using either a binary (yes/no) or a 0–3 grade. The study was a prospective, 4-month duration follow-up of 76 patients with RA requiring anti-tumour necrosis factor (TNF) therapy (complete follow-up data: 66 patients). Intraobserver reliability was evaluated using the intraclass correlation coefficient (ICC), construct validity was evaluated using the Cronbach α test and external validity was evaluated using level of correlation between scoring system and C reactive protein (CRP). Sensitivity to change was evaluated using the standardised response mean. Discriminating capacity was evaluated using the standardised mean differences in patients considered by the doctor as significantly improved or not at the end of the study. Results: Different clinimetric properties of various US scoring systems were at least as good as the clinical scores with, for example, intraobserver reliability ranging from 0.61 to 0.97 versus from 0.53 to 0.82, construct validity ranging from 0.76 to 0.89 versus from 0.76 to 0.88, correlation with CRP ranging from 0.28 to 0.34 versus from 0.28 to 0.35 and sensitivity to change ranging from 0.60 to 1.21 versus from 0.96 to 1.36 for US versus clinical scoring systems, respectively. Conclusion: This study suggests that US evaluation of synovitis is an outcome measure at least as relevant as physical examination. Further studies are required in order to achieve optimal US scoring systems for monitoring patients with RA in clinical trials and in clinical practice.